Puah Reservoir, Malaysia: A Preliminary Limnological Finding at the Newly Operated Hulu Terengganu Hydroelectric Project (HTHEP) - Alyaa Filza Effendi; M K Abubakar; A S Ruddin; A N Saidin; S M Husin; A Md Shukor (Indonesian Society of Limnology, 2022)
In this study we present a first limnological characterization of Puah Reservoir (surface area of 69.79km2) since completion in 2014 and filling in 2015. The results obtained from seven sampling points shows the overall average values, standard deviation and range (min – max) of the physico-chemical parameters investigated in Puah Reservoir for twelve (12) months (Jan – Dec 2016) sampling. Puah Reservoir overall average surface water parameters recorded are water temperature (29.83 ± 1.78 ?C ; 24.10 – 33.70 ?C); dissolved oxygen (DO) (6.17 ± 0.95 mg/L ; 4.00 – 8.74 mg/L); chemical oxygen demand (COD) (17.67 ± 8.18 mg/L ; 2.00 – 39.00 mg/L), biological oxygen demand (BOD) (2.41 ± 1.38 mg/L ; 0.30 – 6.90 mg/L), pH (6.73 ± 0.47 ; 5.79 – 8.51), total suspended solid (TSS) (3.62 ± 2.23 mg/L ; 1.10 – 16.50 mg/L); nitrate (NO3-) (0.01 ± 0.01 mg/L ; 0.00 – 0.04 mg/L), nitrite (NO2-) (1.14 ± 0.88 mg/L; 0.00 – 4.00 mg/L); phosphorus (PO4-) (0.48 ± 0.28 mg/L ; 0.18 – 1.40 mg/L) and ammonia-N (NH4-N) (0.19 ± 0.15 mg/L ; 0.00 – 0.70 mg/L). Calculation of Water Quality Index (WQI) based on six (6) parameters shows that sampling stations at Puah Reservoir are in Class II with an average of 87.58 (Class II). Based on WQI for Class II, it has been proposed suitable for recreational activities involving the body contact, drinking water resources with conventional treatment and suitable for sensitive aquatic species. In summary, thermal stratification in Puah Reservoir was identified within range of 2 – 5 meter vertical depth.